A robust luminescent assay for screening alkyladenine DNA glycosylase inhibitors to overcome DNA repair and temozolomide drug resistance - Ying-Qi Song; Guo-Dong Li; Dou Niu; Feng Chen; Shaozhen Jing; Vincent Kam Wai Wong; Wanhe Wang; Chung-Hang Leung (Elsevier, 2023)
Temozolomide (TMZ) is an anticancer agent used to treat glioblastoma, typically following radiation therapy and/or surgical resection. However, despite its effectiveness, at least 50% of patients do not respond to TMZ, which is associated with repair and/or tolerance of TMZ-induced DNA lesions. Studies have demonstrated that alkyladenine DNA glycosylase (AAG), an enzyme that triggers the base excision repair (BER) pathway by excising TMZ-induced N3-methyladenine (3meA) and N7-methylguanine lesions, is overexpressed in glioblastoma tissues compared to normal tissues. Therefore, it is essential to develop a rapid and efficient screening method for AAG inhibitors to overcome TMZ resistance in glioblastomas. Herein, we report a robust time-resolved photoluminescence platform for identifying AAG inhibitors with improved sensitivity compared to conventional steady-state spectroscopic methods. As a proof-of-concept, this assay was used to screen 1440 food and drug administration-approved drugs against AAG, resulting in the repurposing of sunitinib as a potential AAG inhibitor. Sunitinib restored glioblastoma (GBM) cancer cell sensitivity to TMZ, inhibited GBM cell proliferation and stem cell characteristics, and induced GBM cell cycle arrest. Overall, this strategy offers a new method for the rapid identification of small-molecule inhibitors of BER enzyme activities that can prevent false negatives due to a fluorescent background.